Compact Planar UWB Antenna with Dual Notched Bands Using Slotted Conductorbacked Plane - MOOSAZADEH, Mahdi; ESMATI, Zahra (International Journal of Natural and Engineering Sciences, 2019)
A compact design of a coplanar waveguide fed (CPW-Fed) monopole antenna with ultra wideband (UWB) performance and dual bandnotched characteristics is proposed. Dual band-notched characteristics are achieved by U-shaped slot inside the slotted conductor-backed-plane and a pair of mirror rectangular-shaped slots at the two sides of the truncated conductor-backed plane. The proposed antenna has a small size of 18 ×18 mm2 , and measured to cover the bandwidth for UWB ( 2.7-14.5 GHz) for VSWR<2, except the bandwidths of 3.1-3.6 for WiMAX and 5-6 GHz for WLAN. The antenna has an omnidirectional radiation across the whole ultrawideband as validated by the measured radiation pattern and gain.